A EuIII-based coordination polymer: crystal structure and anti-colon cancer activity. Issue 12 (29th September 2021) - Xu, Wen-Long; Sun, Qi; Gao, Chun-Dong; Zhang, Neng-Wei
Abstract: A novel coordination polymer (CP) {[Eu(HL)]·2(H2 O)}n (1 ) contains luminescent Eu III ion as the metal node on the basis of a bis-(imidazole-4, 5-dicarboxylate) ligand (H4 L) was synthesized via reaction of H4 L and Eu(NO3 )3 ·6H2 O using sodium hydroxide as pH regulator under the hydrothermal condition. The inhibitory activity of compound on SW16 (human colon cancer cells) with squamous shape was further evaluated. Reverse transcription polymerase chain reaction (RT-PCR) was used to assess Tribbles homolog 3 ( trib3 ) gene relative expression level after compound treatment. Besides, Cell Counting Kit-8 (CCK-8) was used to detect the proliferation of SW16 colon cancer cells, and transwell was performed to detect the migration and invasion ability of SW16 cells. Ultimately, the results of molecular docking simulation reveal the interaction of Tribbles homolog 3 (TRIB3) protein and Eu III metallic complex. Graphical Abstract: UF0001 A Eu III -coordination polymer has been prepared under the hydrothermal condition. The inhibitory activity of compound on human oral squamous cell carcinoma cells HSC-4 with squamous shape was further evaluated.